2001
DOI: 10.1037/0022-006x.69.2.227
|View full text |Cite
|
Sign up to set email alerts
|

Relaxation and sleep compression for late-life insomnia: A placebo-controlled trial.

Abstract: Older adults with insomnia were recruited from the community and randomized to treatments: relaxation, sleep compression, and placebo desensitization. Questionnaire data collected at baseline, posttreatment, and 1-year follow-up and polysomnography data collected at baseline and follow-up yielded the following conclusions: All treatments improved self-reported sleep, but objective sleep was unchanged. Clinical significance analyses yielded the strongest findings supporting the active treatments and suggested t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
100
0
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(103 citation statements)
references
References 38 publications
0
100
0
3
Order By: Relevance
“…32 The most significant modifications to traditional CBT-I included (1) substitution of sleep compression 33 in place of sleep restriction therapy and (2) modifications of standard stimulus control instructions (eg, no instruction to get out of bed at night due to high fall risk among ADHC participants). 33 To implement sleep compression (rather than sleep restriction), the initial time in bed window was set to equal the number of hours the patient was spending in bed (rather than the number of hours of sleep). That was then gradually reduced by 15-30 minutes per week until sleep quality improved without increasing daytime sleepiness.…”
Section: Interventionmentioning
confidence: 99%
“…32 The most significant modifications to traditional CBT-I included (1) substitution of sleep compression 33 in place of sleep restriction therapy and (2) modifications of standard stimulus control instructions (eg, no instruction to get out of bed at night due to high fall risk among ADHC participants). 33 To implement sleep compression (rather than sleep restriction), the initial time in bed window was set to equal the number of hours the patient was spending in bed (rather than the number of hours of sleep). That was then gradually reduced by 15-30 minutes per week until sleep quality improved without increasing daytime sleepiness.…”
Section: Interventionmentioning
confidence: 99%
“…For patients with mTBI, we recommend using simplified sleep diary and handouts to suit the patient's concentration problems. Another example is training on when and how to modify SC and SRT through use of alternatives such as sleep compression [35][36][37] and countercontrol. 38 This may be indicated for some chronic pain patients who may find it too physically demanding to move to another room or even get out of bed when unable to sleep.…”
Section: Which Comorbidities Other Than Sleep Disorders To Cover Andmentioning
confidence: 99%
“…If napping does not alleviate daytime sleepiness sufficiently to permit the patient to function safely during the day and evening, we recommend relaxing SRT. For example, setting the initial TIB to be average TST plus 30 min 52,63 or using sleep compression, 64 a variant of SRT that involves gradual, rather than abrupt reduction of TIB. These variations of the standard SRT were also recommended for certain frail patients, patients with chronic pain, and patients who respond to SRT with high levels of anxiety.…”
Section: Which Comorbidities Other Than Sleep Disorders To Cover Andmentioning
confidence: 99%
“…In one of the studies objective sleep was unchanged after relaxation, sleep compression or placebo desensitization, although all treatments improved subjective sleep quality. 32 Nevertheless, in another study, CBT showed better sleep efficiency in PSG than in patients taking zopiclone. In the same study, the CBT group exhibited an increase in sleep stages 3 and 4 and a decrease in time awake during the PSG as compared to the zopiclone or placebo groups.…”
Section: Polysomnography (Psg)mentioning
confidence: 99%
“…However, some treatments, like relaxation or sleep compression, did not lead to improvements in objective sleep. 32 Considering the side effects of hypnotic drugs, especially in elderly patients, research on mind-body interventions in hypnotic drug dependents is very relevant. 13 Both studies on this topic showed that these interventions can ameliorate sleep quality 24 and reduce the use of hypnotic drugs.…”
Section: General Commentsmentioning
confidence: 99%